Deutschsprachige Artikel zur slawistischen Sprachwissenschaft als Mittel der fachlichen und sprachlichen Sozialisation – eine problematische Annäherung an die Disziplin - Doleschal, Ursula; Scherling, Anzhelika (Linguistik Online, 2016)
Research articles are studied by several branches of Applied Linguistics, such as text linguistics, stylistics, foreign language teaching or contrastive rhetoric. However, articles written in German have been scarcely investigated so far. In this contribution we study German articles in Slavic linguistics with regard to their use for the socialization of students into academia. We investigate the presence of the following contents as well as their position of occurrence in the texts: research question, methods and theoretical background. Thus we evaluate, if such articles are an adequate means to introduce students to the way the results of research are brought about. Our study shows that research questions are usually explicitly stated, while methods and theoretical background may remain implicit. It seems that the degree of implicitness relates to the degree of “traditionality” of the research involved, i. e., if the article is, e. g., a philological or a sociolinguistic one.